PERAN GURU BK DALAM MEMBANGUN KEPERCAYAAN DIRI SISWA TERHADAP PILIHAN KARIER DI SMA NEGERI 1 KUDUS - Diana Indah Indraswati; Arina Fithriyana (UIN Sunan Kalijaga Yogyakarta, 2025)
Students' confidence in making career choices is an important aspect of readiness for the future. However, not all students have strong confidence in their potential and career decisions. This study aims to examine the role of Guidance and Counseling teachers in building the confidence of grade XII students at SMA Negeri 1 Kudus related to career choices. The data collection technique used a descriptive qualitative approach through interviews, observations, and documentation. The results showed that the Guidance and Counseling teacher acts as a motivator, mediator, and facilitator in recognizing students' potential, overcoming psychological barriers, and helping to make career selection decisions in accordance with interests and talents. Counseling services are provided individually and in groups with humanistic and cognitive-behavioral approaches, which are effective in increasing students' self-confidence. Support from the school environment and parental involvement also strengthened the career mentoring process. The conclusion of this study confirms that the role of Guidance and Counseling teachers is very strategic in shaping self-confidence which is a key factor in students' readiness to face the future. Keywords: guidance and counseling, self-confidence, career choice.